Leaf accumulation of trace elements and polycyclic aromatic hydrocarbons (PAHs) in Quercus ilex L. - De Nicola, F.; Maisto, G.; Prati, M. V.; Alfani, A. (Environmental pollution (Barking, Essex : 1987), 2008)
Quercus ilex L. leaves were collected four times in one year at six urban sites and one remote area in order to determine trace element and PAH accumulation through concomitant analyses of unwashed and water-washed leaves. Both unwashed and washed leaves showed the highest amounts of trace elements and PAHs in the urban area. Unwashed leaves showed greater differences between urban and remote areas and among the urban sites than washed leaves for trace element and PAH concentrations. Water-washing resulted in a significant (P<0.001) decrease in leaf concentrations of Cr, Cu, Fe, Pb, V and Zn. By contrast, Cd and total PAH concentrations showed no differences between unwashed and washed leaves.
The following values have no corresponding Zotero field: accession-num: 17892907
Keywords: Air Pollutants; Air Pollutants: analysis; Aromatic; Aromatic: analysis; Atomic; biomonitoring; cadmium; Cadmium: analysis; chromium; Chromium: analysis; Cities; copper; Copper: analysis; Environmental Monitoring; Environmental Monitoring: methods; Iron; Iron: analysis; Italy; lead; Lead: analysis; PAHs; Plant Leaves; Plant Leaves: chemistry; Polycyclic Hydrocarbons; Quercus; Quercus ilex L.; Spectrophotometry; Trace Elements; Trace Elements: analysis; Unwashed and washed leaves; Vanadium; Vanadium: analysis; Zinc; Zinc: analysis

Leaf accumulation of trace elements and polycyclic aromatic hydrocarbons (PAHs) in Quercus ilex L. - De Nicola, F; Maisto, G; Prati, M V; Alfani, a (Environmental pollution (Barking, Essex : 1987), 2008)
Quercus ilex L. leaves were collected four times in one year at six urban sites and one remote area in order to determine trace element and PAH accumulation through concomitant analyses of unwashed and water-washed leaves. Both unwashed and washed leaves showed the highest amounts of trace elements and PAHs in the urban area. Unwashed leaves showed greater differences between urban and remote areas and among the urban sites than washed leaves for trace element and PAH concentrations. Water-washing resulted in a significant (P<0.001) decrease in leaf concentrations of Cr, Cu, Fe, Pb, V and Zn. By contrast, Cd and total PAH concentrations showed no differences between unwashed and washed leaves.
Keywords: Air Pollutants; Air Pollutants: analysis; Aromatic; Aromatic: analysis; Atomic; biomonitoring; cadmium; Cadmium: analysis; chromium; Chromium: analysis; Cities; copper; Copper: analysis; Environmental Monitoring; Environmental Monitoring: methods; Iron; Iron: analysis; Italy; lead; Lead: analysis; PAHs; Plant Leaves; Plant Leaves: chemistry; Polycyclic Hydrocarbons; Quercus; Quercus ilex L.; Spectrophotometry; Trace Elements; Trace Elements: analysis; Unwashed and washed leaves; Vanadium; Vanadium: analysis; Zinc; Zinc: analysis

Introduction of the factor of partitioning in the lithogenic enrichment factors of trace element bioaccumulation in plant tissues. - Sardans, Jordi; Penuelas, Josep (Environmental monitoring and assessment, 2006)
Bioindicators are widely used in the study of trace elements inputs into the environment and great efforts have been conducted to separate atmospheric from soil borne inputs on biomass accumulation. Many monitoring studies of trace element pollution take into account the dust particles located in the plant surface plus the contents of the plant tissues. However, it is usually only the trace element content in the plant tissues that is relevant on plant health. Enrichment factor equations take into account the trace element enrichment of biomasses with respect soil or bedrocks by comparing the ratios of the trace element in question to a lithogenic element, usually Al. However, the enrichment equations currently in use are inadequate because they do not take into account the fact that Al (or whichever reference element) and the element in question may have different solubility-absorption-retention levels depending on the rock and soil types involved. This constrain will become critical when results from different sites are compared and so in this article we propose that the solubility factors of each element are taken into account in order to overcome this constrain. We analysed Sb, Co, Ni, Cr, Pb, Cd, Mn, V, Zn, Cu, As, Hg, and Al concentration in different zones of Catalonia (NE Spain) using the evergreen oak Quercus ilex and the moss Hypnum cupressiforme as target species. We compared the results obtained in rural and non industrial areas with those from the Barcelona Metropolitan Area. We observed differences in Al concentrations of soils and bedrocks at each different site, together with the differences in solubility between Al and the element in question, and a weak correlation between total soil content and water extract content through different sites for most trace elements. All these findings show the unsuitability of the current enrichment factors for calculating lithospheric and atmospheric contributions to trace element concentrations in biomass tissues. The trace element enrichment factors were calculated by subtracting the part predicted by substrate composition (deduced from water extracts from soils and bedrock) from total concentrations. Results showed that for most of the trace elements analysed, trace elements enrichment factors were higher inside the Barcelona Metropolitan Area than outside, a finding that indicates that greater atmospheric inputs occur in urban areas. The results show that the most useful and correct way of establishing a reference for lithospheric and atmospheric inputs into the plant tissues is, first, to analyse samples of the same plant species collected from a number of sites possessing similar environmental conditions (climate, vegetation type, soil type) and, second, to use this new enrichment factor obtained by subtracting from the total concentration in plant tissue the predicted contribution of soil or bedrock extracts instead of that of total soil or bedrock concentrations.
Keywords: biomass; Bryopsida; Bryopsida: chemistry; Bryopsida: growth & development; Environmental Monitoring; Environmental Monitoring: methods; Plant Leaves; Plant Leaves: chemistry; Plant Leaves: growth & development; Quercus; Quercus: chemistry; Quercus: growth & development; Soil Pollutants; Soil Pollutants: analysis; Spain; Trace Elements; Trace Elements: analysis

Introduction of the factor of partitioning in the lithogenic enrichment factors of trace element bioaccumulation in plant tissues. - Sardans, Jordi; Penuelas, Josep (Environmental monitoring and assessment, 2006)
Bioindicators are widely used in the study of trace elements inputs into the environment and great efforts have been conducted to separate atmospheric from soil borne inputs on biomass accumulation. Many monitoring studies of trace element pollution take into account the dust particles located in the plant surface plus the contents of the plant tissues. However, it is usually only the trace element content in the plant tissues that is relevant on plant health. Enrichment factor equations take into account the trace element enrichment of biomasses with respect soil or bedrocks by comparing the ratios of the trace element in question to a lithogenic element, usually Al. However, the enrichment equations currently in use are inadequate because they do not take into account the fact that Al (or whichever reference element) and the element in question may have different solubility-absorption-retention levels depending on the rock and soil types involved. This constrain will become critical when results from different sites are compared and so in this article we propose that the solubility factors of each element are taken into account in order to overcome this constrain. We analysed Sb, Co, Ni, Cr, Pb, Cd, Mn, V, Zn, Cu, As, Hg, and Al concentration in different zones of Catalonia (NE Spain) using the evergreen oak Quercus ilex and the moss Hypnum cupressiforme as target species. We compared the results obtained in rural and non industrial areas with those from the Barcelona Metropolitan Area. We observed differences in Al concentrations of soils and bedrocks at each different site, together with the differences in solubility between Al and the element in question, and a weak correlation between total soil content and water extract content through different sites for most trace elements. All these findings show the unsuitability of the current enrichment factors for calculating lithospheric and atmospheric contributions to trace element concentrations in biomass tissues. The trace element enrichment factors were calculated by subtracting the part predicted by substrate composition (deduced from water extracts from soils and bedrock) from total concentrations. Results showed that for most of the trace elements analysed, trace elements enrichment factors were higher inside the Barcelona Metropolitan Area than outside, a finding that indicates that greater atmospheric inputs occur in urban areas. The results show that the most useful and correct way of establishing a reference for lithospheric and atmospheric inputs into the plant tissues is, first, to analyse samples of the same plant species collected from a number of sites possessing similar environmental conditions (climate, vegetation type, soil type) and, second, to use this new enrichment factor obtained by subtracting from the total concentration in plant tissue the predicted contribution of soil or bedrock extracts instead of that of total soil or bedrock concentrations.
The following values have no corresponding Zotero field: accession-num: 16648953
Keywords: biomass; Bryopsida; Bryopsida: chemistry; Bryopsida: growth & development; Environmental Monitoring; Environmental Monitoring: methods; Plant Leaves; Plant Leaves: chemistry; Plant Leaves: growth & development; Quercus; Quercus: chemistry; Quercus: growth & development; Soil Pollutants; Soil Pollutants: analysis; Spain; Trace Elements; Trace Elements: analysis

Trace metal biomonitoring in the soil and the leaves of Quercus ilex in the urban area of Naples. - Alfani, a; Bartoli, G.; Rutigliano, F. a; Maisto, G.; De Santo, a V. (Biological trace element research, 1996)
The concentrations of Pb, Cu, Fe, and Mn were analyzed in surface deposit and tissue of Quercus ilex leaves from several sites of the urban area of Naples, exposed to different degrees of air pollution. These included some major roads with heavy traffic loads, squares, and three urban parks. The soil from the trunk base area of Q. ilex trees in the same sites was also analyzed for total and available metal contents. Pb, Cu, and Fe contents in the surface deposit and leaf tissue were significantly higher (p < 0.01) in leaves from roadside sites than in leaves from parks; significant correlations were found between deposit- and tissue-contents of Pb, Cu, and Fe. Mn content in leaves from roadside sites and in leaves from parks were similar and Mn content in the leaf deposit was irrelevant. Significant differences (p < 0.001) in both total and available Pb and Cu soil content were found between sampling sites. Also for available Fe and Mn soil content differences among sites were relevant, although the highest values were measured in soil from urban parks. A positive correlation between leaf and soil metal content was found only for Pb, thus suggesting that trace metal contents of leaves directly depend on atmospheric depositions. Seasonal variations of Pb, Cu, and Fe were pronounced at a polluted site, whereas no relevant seasonal variation was observed at a control site; moreover, metal accumulation was high at the polluted site. Mn content and seasonal dynamics were comparable at control and polluted sites.
The following values have no corresponding Zotero field: accession-num: 8834387
Keywords: Air Pollutants; Air Pollutants: analysis; biomonitoring; copper; Copper: analysis; Environmental Monitoring; Holly Oak; Iron; Iron: analysis; lead; Lead: analysis; leaves; Manganese; Manganese: analysis; Plants; Plants: chemistry; seasonal dynamics; Soil; Soil: analysis; Trace Elements; Trace Elements: analysis; urban area pollution

Trace metal biomonitoring in the soil and the leaves of Quercus ilex in the urban area of Naples. - Alfani, a; Bartoli, G; Rutigliano, F a; Maisto, G; De Santo, a V (Biological trace element research, 1996)
The concentrations of Pb, Cu, Fe, and Mn were analyzed in surface deposit and tissue of Quercus ilex leaves from several sites of the urban area of Naples, exposed to different degrees of air pollution. These included some major roads with heavy traffic loads, squares, and three urban parks. The soil from the trunk base area of Q. ilex trees in the same sites was also analyzed for total and available metal contents. Pb, Cu, and Fe contents in the surface deposit and leaf tissue were significantly higher (p < 0.01) in leaves from roadside sites than in leaves from parks; significant correlations were found between deposit- and tissue-contents of Pb, Cu, and Fe. Mn content in leaves from roadside sites and in leaves from parks were similar and Mn content in the leaf deposit was irrelevant. Significant differences (p < 0.001) in both total and available Pb and Cu soil content were found between sampling sites. Also for available Fe and Mn soil content differences among sites were relevant, although the highest values were measured in soil from urban parks. A positive correlation between leaf and soil metal content was found only for Pb, thus suggesting that trace metal contents of leaves directly depend on atmospheric depositions. Seasonal variations of Pb, Cu, and Fe were pronounced at a polluted site, whereas no relevant seasonal variation was observed at a control site; moreover, metal accumulation was high at the polluted site. Mn content and seasonal dynamics were comparable at control and polluted sites.
Keywords: Air Pollutants; Air Pollutants: analysis; biomonitoring; copper; Copper: analysis; Environmental Monitoring; Holly Oak; Iron; Iron: analysis; lead; Lead: analysis; leaves; Manganese; Manganese: analysis; Plants; Plants: chemistry; seasonal dynamics; Soil; Soil: analysis; Trace Elements; Trace Elements: analysis; urban area pollution